Collaboration in the Boardroom: Behavioral and Performance Consequences of CEO-Board Social Ties - Westphal, James D. (Academy of Management Journal, 1999)
Empirical research has typically rested on the assumption that board independence from management enhances board effectiveness in administering firms. The present study shows how and when a lack of social independence can increase board involvement and firm performance by raising the frequency of advice and counsel interactions between CEOs and outside directors. Hypotheses were tested with original survey data from 243 CEOs and 564 outside directors on behavioral processes and dynamics in management-board relationships